URGENSI LITERASI DIGITAL DALAM MENANGKAL HOAX INFORMASI KESEHATAN DI ERA DIGITAL - Etik Anjar Fitriarti (Metacommunication: Journal of Communication Studies, 2019)
Many as the number of the community of being exposed to hoax various kinds of health information in this digital era. This clearly need the consciousness of the community itself and requires support to overcome this phenomenon because it can to be harmful and made anxious the doers the public related to false news or hoax in social media. A support for to overcome problems related to this can be conducted one of them is by digital literacy. Even though the community is therefore skillful in digital or social media but also need to be given digital education related to the use of the information that spread in the digital era so that into society who is wise and critical in using social media.